Pemahaman Permintaan Konsumen Dalam Bisnis Internasional - Nabila Annisa Rahmadhani Siregar (Jurnal Publikasi Ilmu Manajemen, 2025)
In today’s modern era, it creates great opportunities for business people, but they are also faced with the threat of increasingly tight business competition. This industrial competition does not only occur within the country but also abroad. So the right strategy is needed to enter the global market and how to understand the various demands that exist in the international market. This research uses qualitative methods using literature studies. This research also analyzes and reviews books, articles, journals and relevant sources related to the research title. Things that must be learned are the need to understand consumer demand, where the company must be able to manage operational management planning so that the business can run effectively and efficiently. Companies also need to research what consumers like and can meet consumer demands. Understanding local culture and consistently providing quality products are also important factors in business success.